A comprehensive assessment of lymphocyte subsets, their prognostic significance, and changes after first-line therapy administration in patients with chronic lymphocytic leukemia - Vodárek, Pavel; Écsiová, Dominika; Řezáčová, Vladimíra; Souček, Ondřej; Šimkovič, Martin; Vokurková, Doris; Belada, David; Žák, Pavel; Smolej, Lukáš (Cancer medicine, 2023)
BACKGROUND: In chronic lymphocytic leukemia (CLL), changes in the peripheral blood lymphocyte subsets play an important role in disease progression and infectious complications. The impact of chemoimmunotherapy (CIT) on these changes has not been extensively studied METHODS: We used multi-color flow cytometry, to prospectively measure absolute and relative numbers of CD4+ and CD8+ T-cells and their subsets in 45 patients with indolent untreated CLL, 86 patients indicated for first-line treatment, and 34 healthy controls. In 55 patients, we analyzed the impact of CIT RESULTS: CLL patients had a significant increase in most cell populations in comparison to controls. Progression of CLL was characterized by significantly elevated counts with the exception of a lower percentage of naïve T-cells. After treatment, the percentage of naïve T-cells further decreased at the expense of effector memory T-cells (TEM). In patients with indolent CLL, higher percentages of naïve CD4+ (p = 0.0026) and naïve CD8+ (p = 0.023) T-cells were associated with a longer time to first treatment (TTFT). The elevation of CD4+ central memory T-cells (TCM) (p = 0.27) and TEM (p = 0.003) counts and a higher percentage of CD4+ TEM (p = 0.0047), were linked with shorter TTFT. In treated patients, increased regulatory T-cells count was associated with shorter time to next treatment (TTNT) (p = 0.042), while higher CD4+ TCM count with shorter TTNT (p = 0.035) and shorter overall survival (p = 0.041). CONCLUSION: Our results indicate that naïve cell depletion and CD4+ TCM and TEM increases are detrimental to CLL patients' prognosis.
Keywords: CLL; T-Lymphocyte Subsets; regulační T-lymfocyty; lymphocyte subset; prognóza; Lymphocyte Subsets; CD8-Positive T-Lymphocytes; T-lymfocyty - podskupiny; immunosuppression; Leukemia, Lymphocytic, Chronic, B-Cell; T-Lymphocytes, Regulatory; CD4-Positive T-Lymphocytes; prognosis; lidé; CD8-pozitivní T-lymfocyty; Humans; chemoimmunotherapy; Prognosis; infections; chronická lymfatická leukemie; podskupiny lymfocytů; CD4-pozitivní T-lymfocyty